Christchurch in the context of New Zealand terrorism and right wing extremism. Issue 3 (2nd September 2019) - Battersby, John; Ball, Rhys
ABSTRACT: This paper sets out to consider Brendon Tarrant in the context of New Zealand terrorism. While Tarrant's attack on 15 March 2019 was unprecedented in terms of its scale, he was in many ways a somewhat typical New Zealand terrorist offender; alone, driven, difficult to detect and able to strike without warning. While Islamist inspired terrorism has been the predominant identified threat in recent years, the primacy of any particular threat historically did not blind New Zealand's security sector to others, and various Right Wing extremist (RWE) risks had been identified, investigated and mitigated periodically since at least 1990. This study is based on an historical overview of terrorism in New Zealand, as well as interviews with security sector practitioners, who recalled their experiences of RWE risk. Those practitioners responsible for the detection and mitigation of terrorism risk in New Zealand genuinely seemed to sense that RWE risk was increasing, but were fettered in their abilities to counter it by the inconsistency it presented and a general, societal complacency about the risk of terrorism in New Zealand.